What's good in the neighbourhood? Examining the wellbeing impacts of urban regeneration using administrative data - Kirkpatrick, Linda; Pacheco, Gail; Schober, Thomas; Meehan, Lisa (International Journal of Population Data Science, 2026)
New Zealand (NZ) faces substantial housing challenges with a housing crisis brought on by housing shortages, rising housing costs, poor quality stock and overcrowding issues. Kāinga Ora is the primary government agency responsible for social housing and urban development in NZ. Kāinga Ora has further plans to increase the housing supply by 35,000 homes over the next 15 years, with 50% of these homes to be delivered in Auckland. These investments aim to improve wellbeing, liveability, social connections, and place-based identity through the provision of affordable homes, shared community spaces and active transport options to support access to employment, amenities and services. By developing or regenerating urban areas (“urban regeneration”) that people live in, there is the potential to improve health and wider social outcomes in affected communities. Urban regeneration has the potential increase housing supply and improve the quality of the current housing stock, thereby having positive long-term impacts on community wellbeing. This research uses detailed housing intensification data from Kāinga to assess the social return-on-investment. This research measures the wellbeing impact of urban regeneration using administrative data and the NZ Treasury’s Living Standards Framework, supplemented by the New Zealand Index of Multiple Deprivation. Wellbeing outcomes of urban regeneration are grouped across three domains: (1) human capital – education and labour market outcomes; (2) physical and mental health and (3) crime and safety. These outcomes are constructed from administrative data from the Integrated Data Infrastructure which is administered by StatsNZ.